3D Imaging of the Early Embryonic Chicken Heart with Focused Ion Beam Scanning Electron Microscopy. (17th April 2014) - Rennie, Monique Y.; Gahan, Curran G.; López, Claudia S.; Thornburg, Kent L.; Rugonyi, Sandra
Abstract: Early embryonic heart development is a period of dynamic growth and remodeling, with rapid changes occurring at the tissue, cell, and subcellular levels. A detailed understanding of the events that establish the components of the heart wall has been hampered by a lack of methodologies for three-dimensional (3D), high-resolution imaging. Focused ion beam scanning electron microscopy (FIB-SEM) is a novel technology for imaging 3D tissue volumes at the subcellular level. FIB-SEM alternates between imaging the block face with a scanning electron beam and milling away thin sections of tissue with a FIB, allowing for collection and analysis of 3D data. FIB-SEM was used to image the three layers of the day 4 chicken embryo heart: myocardium, cardiac jelly, and endocardium. Individual images obtained with FIB-SEM were comparable in quality and resolution to those obtained with transmission electron microscopy. Up to 1, 100 serial images were obtained in 4 nm increments at 4.88 nm resolution, and image stacks were aligned to create volumes 800–1, 500 μ m 3 in size. Segmentation of organelles revealed their organization and distinct volume fractions between cardiac wall layers. We conclude that FIB-SEM is a powerful modality for 3D subcellular imaging of the embryonic heart wall.